ANALYSIS OF SELECTED AREAS OF EDUCATIONAL ACTIVITY OF SENIOR CITIZENS - Gil, Alina; Nowacka, Urszula; Siguencia, Luis Ochoa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aging of the society caused increased interest in problems of the elderly. This article presents the place of seniors in the educational space, defines the selected forms of their educational activity. Education counteracts social exclusion and sense of loneliness, provides access to the amenities of the modern world, allows the seniors to satisfy their need for self-accomplishment. Seniors thus face challenges they have never confronted before, while the age of transformation forces them to engage in continuous education, which becomes not only a duty, but also an obligation. Developing the expected forms of education of the elderly is one of the most vital tasks in the years to come.